Glutathione S-transferases M1-1 and T1-1 as risk modifiers for renal cell cancer associated with occupational exposure to chemicals. Issue 10 (22nd September 2003) - Buzio, L; De Palma, G; Mozzoni, P; Tondel, M; Buzio, C; Franchini, I; Axelson, O; Mutti, A
Abstract : Aims: To investigate the possible interaction between occupational risk factors and genotype for glutathione S-transferases M1 and T1 ( GSTM1 and GSTT1 ) in renal cell cancer (RCC). Methods: One hundred patients with RCC and 200 outpatient controls were enrolled at Parma University Hospital. The polymorphisms of glutathione S-transferase M1-1 ( GSTM1 ) and T1-1 ( GSTT1 ) were investigated by PCR; occupational history was collected by a structured questionnaire. Results: Subjects with GSTM1 present genotype showed higher risks for RCC, compared to GSTM1 null subjects, if exposed to metals (OR 2.73; 95% CI 0.91 to 8.22 v 1.14; 95% CI 0.46 to 2.82) or pesticides (OR 3.46; 95% CI 1.12 to 10.74 v 1.59; 95% CI 0.48 to 5.34). The GSTT1 present genotype also enhanced the risk (about twofold) of RCC among subjects exposed to solvents and pesticides, compared with those GSTT1 null. Conclusions: Results support the hypothesis that GSTM1 and GSTT1 polymorphisms can interact with several occupational exposures to significantly modify the risk of RCC among exposed subjects.